Dynamics of plantation forest development and ecosystem carbon storage change in coastal Bangladesh - Muhammad Ziaul Hoque (Elsevier, 2021)
Plantation forest has an immense potential for significantly contributing to the global carbon cycle for regulating climate change. Assessing the spatio-temporal distribution of plantation forest vegetation by analyzing Landsat land use/land cover (LULC) data can provide a logical basis for developing ecological and environmental policies to effectively manage ecosystem carbon storage in the future. The study aimed at assessing and predicting dynamics of plantation forest development and ecosystem carbon storage change in coastal Bangladesh over 1988–2041 under three future land management scenarios: business-as-usual (BAU), economic development (ED), and ecological protection-afforestation (EPA) by linking CA-Markov and InVEST models. Findings from LULC change analysis revealed that during 1988–2018, plantation forest increased by 984.9 km2 (68.34%) leading to an overall increase in regional carbon storage, of 3.30 Tg C. Over 2018–2041, plantation forest land could be increased by 249.90, 361.24, and 472.14 km2 under the BAU, ED, and EPA scenarios, respectively, that may potentially increase future carbon storage by 0.64 Tg C, 0.91 Tg C, and 3.77 Tg C, respectively. However, the three future land management scenarios may lead to shortages of regional food supply, of 5.96%, 13.69%, and 11.06% respectively. The suitability maps of different LULC types created in this study could be useful to find out the potential areas of plantation forest development in the future and would provide a scientific basis for further discussion by policymakers on future land use planning, to minimize the trade-offs between food security and climate change adaptation.